Been stuck on this question for awhile now and I just don't know how to get Cube(x) so that I can use ^ intro with Cube(x) and ∀y (Cube(y) → y = a) and then use ∃ intro to get the conclusion. This is what I have so far.enter image description here

This is the original question if needed (14.11). enter image description here


Hint: Universal elimination can be to any term in the context, which includes the assumed witness for the existential.

|_ Ex Ay (Cube(y)<->y=x)                Premise
|  |_ [a] Ay (Cube(y)<->y=a)            Assumption
|  |  Cube(a)<->a=a                     Universal Elimination
|  |  :
|  |  :
|  |  Ex (Cube(x) & Ay (Cube(y)->y=x))  Existential Introduction
|  Ex (Cube(x) & Ay (Cube(y)->y=x))     Existential Elimination
| improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.